The UGT1A1*28 gene variant predicts long-term mortality in patients undergoing coronary angiography - Zulus, Barbara; Kleber, Marcus E.; März, Winfried (Clinical chemistry and laboratory medicine, 2018)
Abstract Background: Uridine diphosphate glycosyltransferases 1A1 (UGT1A1) plays an essential role in detoxification and excretion of several endogenous and exogenous compounds. A functional polymorphism in the promoter of the UGT1A1 gene (TA repeat insertion, UGT1A1*28, rs3064744) has been associated with reduced UGT1A1 enzyme activity. The purpose of the present study was to investigate the role of UGT1A1 genotypes in mortality. Methods: UGT1A1 genotypes as well as baseline plasma bilirubin levels were analyzed in participants of the Ludwigshafen Risk and Cardiovascular Health study (n=3316). UGT1A1*28 genotypes were determined on an ABI PRISM 3730 genetic analyzer. Results: As expected, UGT1A1 genotypes were associated with baseline bilirubin levels (*1/*1 genotype: 9.1±4.6 µmol/L; *1/*28 genotype: 10.8±5.3; *28/*28: 16.9±9.2; p<0.001). During a median follow-up of 10.4 years, 995 subjects (30.0%) died. In a multivariate regression analysis adjusting for age, sex, smoking, type 2 diabetes, dyslipidemia, alanine aminotransferase (ALT) levels and bilirubin levels, the UGT1A1*28 variant predicted lower overall mortality (hazard ratio [HR], 0.86; 95% confidence interval [CI], 0.78-0.95; p=0.003). Contrary to expected, higher baseline bilirubin levels predicted increased mortality (HR, 1.014; 95% CI, 1.002-1.025; p=0.019). Conclusions: The UGT1A1*28 gene variant is associated with lower mortality rates. The protective effect of the UGT1A1*28 variant likely includes mechanism other than bilirubin metabolism.